2018
DOI: 10.1111/jfd.12774
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and differentiation of carp oedema virus and cyprinid herpes virus‐3 in koi and common carp

Abstract: Carp oedema virus (CEV) and koi herpes virus (KHV) are of major concern to common carp breeders and koi enthusiasts worldwide. The viruses cause diseases that exhibit similar external signs; thus, it is difficult to distinguish between them clinically. In this study, we developed and optimized rapid and accurate single- and multiplex isothermal diagnostic tools, based on recombinase polymerase amplification (RPA), for detection and differentiation of CEV and KHV. The assays were combined with a lateral flow di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
3
8
1
Order By: Relevance
“…Our results were similar to other studies using lateral flow assay strips for the rapid detection of KHV [ 30 , 31 ]. The latter based their diagnostic systems on the loop mediated isothermal amplification and the isothermal DNA amplification assay using recombinase polymerase amplification [ 30 , 31 ]. In contrast, we based our assay on a more common amplification technique, the PCR.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were similar to other studies using lateral flow assay strips for the rapid detection of KHV [ 30 , 31 ]. The latter based their diagnostic systems on the loop mediated isothermal amplification and the isothermal DNA amplification assay using recombinase polymerase amplification [ 30 , 31 ]. In contrast, we based our assay on a more common amplification technique, the PCR.…”
Section: Discussionsupporting
confidence: 92%
“…The cumulative mortality rate in this case was 20%, which is not consistent with previous reports [15,16,23]. Mortality and morbidity rates unusually decrease when temperatures increase to 28 • C [26], which may explain the lower mortality observed in this case. Nevertheless, some previous reports indicate that KSD occurs at lower temperatures.…”
Section: Discussioncontrasting
confidence: 83%
“…The most common behavioral abnormality of CEV infection in cyprinid fish is lying on the bottom of the ponds. Other clinical signs of infected fish include: lethargy, anorexia, swelling and necrotic gills, enophthalmos, and skin hemorrhages or skin ulceration [23][24][25][26]. Similar clinical signs were observed in the present episode.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, several research groups have studied RPA reaction temperatures that lie outside of the recommended range. 38,44,45,60,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] The largest temperature range was tested between 15°C and 50°C; 62,64,69,70,76 and results indicated the marginal reaction temperature to produce a positive result should be greater than 30°C. [62][63][64]66,67,69,71,74,76,77 However, Sun et al 65 and Poulton and Webster 60 showed that temperature as low as 25°C could still generate a positive signal after RPA amplification and subsequent lateral flow strip detection.…”
Section: Influence Of Temperature and Agitationmentioning
confidence: 99%